Prevention of Deep Venous Thromboembolism. (5th September 2018) - Grabo, Daniel J; Seery, Jason M; Bradley, Matthew; Zakaluzny, Scott; Kearns, Michel J; Fernandez, Nathanial; Tadlock, Matthew
Abstract: The nature of many combat wounds puts patients at a high risk of developing deep venous thrombosis (DVT) and pulmonary embolism (PE), which fall under the broader disease category of venous thromboembolism (VTE). In addition to the hypercoagulable state induced by trauma, massive injuries to the extremities, prolonged immobility, and long fixed wing transport times to higher echelons of care are unique risk factors for venous thromboembolism in the combat-injured patient. These risk factors mandate aggressive prophylaxis for DVT and PE that can effectively be achieved by the use of lower extremity sequential compression devices and low dose unfractionated heparin or low molecular weight heparin. In addition, inferior vena cava filters are often used for PE prophylaxis when chemical DVT prophylaxis fails or is contraindicated. The following Department of Defense (DoD) Joint Trauma System (JTS) Clinical Practice Guideline (CPG) discusses the current recommendations for the prevention of DVT and PE including the use of inferior vena cava filters (IVCFs).